Efficacy and safety of oxaliplatin-based hyperthermic intraperitoneal chemotherapy with secondary cytoreduction for platinum resistant recurrent ovarian cancer: A single-center retrospective cohort study - Hua-Hsi Wu; Peng-Hui Wang; Yi-Jen Chen; Wei-Ting Chao (Journal of the Formosan Medical Association, 2025)
Background/purpose: This retrospective study evaluated the efficacy and adverse effects of oxaliplatin-based hyperthermic intraperitoneal chemotherapy (HIPEC) with secondary cytoreductive surgery (CRS) in patients with recurrent ovarian cancer. Methods: Patients diagnosed with recurrent epithelial ovarian cancer, including fallopian tube and peritoneal origin, who underwent oxaliplatin-based HIPEC with secondary CRS, were enrolled. The primary outcome was progression-free survival (PFS), and the secondary outcomes were overall survival (OS) and adverse events. Results: A total of 33 patients were included in the analysis. The mean PFS and OS were 20.4 months (95% CI 16.3–24.5 months) and 26.7 months (95% CI 23.7–29.7), respectively. Furthermore, the OS and PFS between platinum-sensitive and resistant recurrence showed no significant difference. Univariate and multivariate analysis of PFS identified a pre-operative peritoneal carcinomatosis index (PCI) score of ≥5 as a poor prognostic factor. Among them, the incidence of acute kidney injury was 9.0 % & none had grade ≧3 adverse events. Conclusion: Oxaliplatin-based HIPEC with secondary CRS might provide a survival benefit for patients with recurrent ovarian cancer with a decreased incidence of renal toxicity compared to cisplatin-based regimens. It might be effective and feasible in selected recurrent ovarian cancer patients, regardless of platinum-sensitive or resistant.